Respuestas
Respuesta dada por:
2
Demostrar
senx + tanx
----------------- = tanx (tanx = senx /cosx) Reemplazas
1 + cosx
senx + senx/cosx
-------------------------- = tanx
1 + cosx
senxcosx + senx
---------------------------
cosx
----------------------------- = tanx
1+ cox
senxcosx + senx sacas factor comun senx
------------------------- = tanx
cosx(1 + cosx)
senx(cosx + 1)
----------------------- = tanx Simplificas cosx + 1
cosx( 1 + cosx)
senx
-------- = tanx Pero senx / cosx = tanx reemplazas
cosx
tanx = tanx
senx + tanx
----------------- = tanx (tanx = senx /cosx) Reemplazas
1 + cosx
senx + senx/cosx
-------------------------- = tanx
1 + cosx
senxcosx + senx
---------------------------
cosx
----------------------------- = tanx
1+ cox
senxcosx + senx sacas factor comun senx
------------------------- = tanx
cosx(1 + cosx)
senx(cosx + 1)
----------------------- = tanx Simplificas cosx + 1
cosx( 1 + cosx)
senx
-------- = tanx Pero senx / cosx = tanx reemplazas
cosx
tanx = tanx
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años